ISSUES OF IMPROVING STATE POLICY IN THE FIELD OF COMBATING CORRUPTION IN UZBEKISTAN - Aliyev Bekdavlat (Sciental Journals Publishing, 2025)
The article analyzes the state policy, legislative reforms and international experiences in combating corruption in Uzbekistan. On the initiative of President Shavkat Mirziyoyev, a wide range of measures are being implemented in this area, including: the establishment of an Anti-Corruption Agency, the introduction of the E-Anticor.uz electronic platform and mobile applications, the establishment of a compliance control system in all state bodies, and the expansion of communication with the public in the activities of the Ombudsman. The article also studies the experience of countries such as Singapore, the USA, Canada, Denmark and Finland. It is noted that the introduction of such effective systems will help reduce corruption.
Keywords: Corruption, Fight against corruption, Public policy, Compliance control, Anti-corruption agency, E-Anticor.uz, Code of Ethics, Officials, Property declaration, Public control, Public service, Legislative reforms, Transparency, Transparency, Ombudsman, International ratings, Civil society